Medicalization of Rural Poverty: Challenges for Access. Issue 3 (September 2018) - Weeks, Elizabeth
This article provides a broad survey of issues facing rural communities and suggests that medicalization of poverty concepts and interventions need to be tailored to those populations. Rural poverty may be both broader and deeper than in urban areas. Those challenges seem to produce a constellation of health conditions, as rural residents struggle with unemployment and lack of opportunities. Relatedly, rural communities struggle to maintain financially viable hospitals and specialty providers. The article closes by offering a snapshot of rural-specific strategies to address these issues.